(untitled) (Academia Science Repository, 2023)
The repercussions of the extensive geographical discoveries have led to significant geopolitical changes in the second half of the 20th century, resulting in a transformation on a global scale. As one of the most prominent colonial powers in history, Great Britain’s sovereignty over its colonies has been challenged due to the effects of these changes. Over the years, the relationship between the "metropole" and the "colony" has evolved into a complex system that cannot be easily categorized into separate parts. With the help of new methods and approaches, the "former metropole - former colony" relations have been redefined to prevent complete separation of the threads that have woven the system. Great Britain has employed various techniques and means to maintain its ties with its former colonies, utilizing different methods and approaches as outlined in this article through a scholarly analysis.